Controlling Our Destiny : A Board Member's View of Deaf President Now - Bravin, Philip W. (Book collections on Project MUSE., 2020)
"An insider's view of the events that lead up to one of the most crucial moments in American deaf history: the 1988 Deaf President Now (DPN) protests at Gallaudet University"--